Towards better understanding the challenges of reliable and trust-aware critical communications in the aftermath of disaster - Radenkovic, Milena; Walker, Adam; Bai, Li (2018)
This paper seeks to better understand the highly multi-dimensional, multi-faceted challenges of meeting trust and reliability requirements in critical, disaster aftermath communication networks comprising heterogeneous groups of nodes. Through emulation of a UK based flooding event in the South of England we show the impact of selfish and malicious nodes on disaster communications when disparate, distributed, and disconnected nodes are carrying sensitive messages relating to resource availability and need. To further support the need for trust-aware schemes in such environments we compare benchmark DTN protocols against our reliable, trust-aware framework, TACID, which penalises and excludes malicious nodes. We show that in disaster aftermath networks trust-aware schemes can significantly reduce the impact of malicious intermediary nodes and increase overall reliability whilst simultaneously maintaining message confidentiality.